Tari Karawitan Manifestasi Simbol Aristokrat Priangan - Nugraha, Dea (PANTUN: Jurnal Ilmiah Seni Budaya, 2019)
Kawitan dance is one of the genres of Keurseus dance created in Priangan Aristocratic society. This study tries to reveal textual and contextual elements in Karawitan Dance. Ernst Cassirers symbol theory is applied to study the Priangan aristocrat symbols on Kawitan dance. Most of the main source persons of this study have passed away. Therefore, the interviews are conducted to etic persons who ever became the dancer or the testator of Kawitan Dance. The data of Kawitan Dance performances are taken from documentation. Meanwhile, the observation is conducted to studio, school, or higher institution which put Kawitan Dance as one of their learning materials. The elements of Kawitan Dance such as dance movement, dance structure, costume, staging style, and gamelan show symbol relation depicting the characteristics of menak priyai called Priangan Aristocrat.Keywords: Kawitan Dance, Aristocrat, Symbol